The reliability of cold region tunnels considering deterioration of the insulation layer. - Jianqing Jia; Shaohua An; Victor O Tenorio (PLoS ONE)
Frost heave is a most common form of tunnel defect in cold regions. Installing an insulation layer is a key solution. However, the insulation layer deteriorates with freeze-thaw cycles and temperature changes. These significantly impact tunnel reliability in these areas. To determine the influence of insulation layer deterioration and temperature change to reliability of cold region tunnel, this paper examines a tunnel in the Qinghai-Tibet Plateau. It uses projected temperature increases of 2.6 °C and 4 °C over the next 50 years as boundary conditions. The study analyzes the evolution of freeze-thaw thickness, temperature fields, and stress fields in the surrounding rock. It considers both scenarios: with and without insulation layer deterioration. Using the Monte-Carlo method, the study investigates the variation in tunnel reliability. The results indicate that, with insulation layer deterioration, freeze-thaw thickness, temperature fields, and stress fields in the surrounding rock increase under both temperature scenarios. Consequently, tunnel reliability decreases. Specifically, with temperature increases of 2.6 °C and 4 °C, tunnel reliability decreases by approximately 4.5% and 6.3%, respectively, when considering insulation layer deterioration.